Developing an Assessment Method of Active Aging: University of Jyvaskyla Active Aging Scale. (July 2019) - Rantanen, Taina; Portegijs, Erja; Kokko, Katja; Rantakokko, Merja; Törmäkangas, Timo; Saajanaho, Milla
Objective: To develop an assessment method of active aging for research on older people.Method: A multiphase process that included drafting by an expert panel, a pilot study for item analysis and scale validity, a feedback study with focus groups and questionnaire respondents, and a test–retest study. Altogether 235 people aged 60 to 94 years provided responses and/or feedback.Results: We developed a 17-item University of Jyvaskyla Active Aging Scale with four aspects in each item (goals, ability, opportunity, and activity; range 0-272). The psychometric and item properties are good and the scale assesses a unidimensional latent construct of active aging.Discussion: Our scale assesses older people's striving for well-being through activities pertaining to their goals, abilities, and opportunities. The University of Jyvaskyla Active Aging Scale provides a quantifiable measure of active aging that may be used in postal questionnaires or interviews in research and practice.